Bias in counseling of seizure patients following a transient impairment of consciousness: Differential adherence to driver fitness guidelines. (August 2015) - Jirsch, Jeffrey; Siddiqi, Maria; Smyth, Penelope; Maximova, Katerina
Highlights: Seizure clinic referrals are variably counseled about driving safety in the community. We examined counseling and driving habits prior to initial neurological assessment. Seizure patient drivers have been counseled more frequently than other unfit drivers. Seizure patients have ceased driving more frequently than other unfit drivers. Public health and quality of life effects may stem from physicians' biases. Abstract: Purpose: To determine primary care physicians' counseling as well as patients' driving behaviors following seizure and non-seizure events impairing consciousness in the community. Methods: Patients attending a rapid-referral first seizure clinic were entered into the study if they were deemed medically-unfit to drive according to national guidelines for driving licensure: had experienced a seizure or an unexplained episode of lost consciousness, and had a valid driver's license at the time of their index event. Risk of physician counseling in the community regarding driving cessation in the interval between initial primary care assessment and neurological consultation was examined as a primary outcome, and patient driving cessation was examined as a secondary outcome. Results: 106 of 192 (55%) patients attending clinic met guideline criteria requiring driver fitness counseling in the primary care community, and 89 patients (46%) were deemed medically-unfit to drive following the initial specialist consultation appointment. Among medically unfit driver cases, 73% were ultimately deemed to have experienced a seizure and 27% had experienced a non-seizure event (e.g. syncope, PNES). Driver fitness counseling was more likely for seizure than non-seizure cases (unadjusted odds ratio: 4.14, p < 0.05), as was patient driving cessation (5.10, p < 0.05). Conclusion: Physician compliance with clinical practice guidelines appears strongly biased when counseling about driving following an episode of transient impairment in consciousness. The failure of the primary care medical community to apply driver fitness counseling equitably to both seizure and non-seizure drivers may have ramifications upon public safety or conversely disease-related quality-of-life.